Total Phenolic, Flavonoid, Tannin Content and DPPH Scavenging Activity of Caesalpinia sappan Linn. Bark - Brandon Aristo Verick Purba; Rini Pujiarti; Masendra Masendra; Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2022)
Caesalpinia sappan is a shrubby Leguminosae tree commonly found in Indonesia, traditionally utilized as natural dye and herbal drink. However, in the making of traditional herbal drink, the bark is often discarded as residues. This research aimed to investigate total phenolic (TPC), flavonoid (TFC), and tannin (TTC) content as well as the antioxidant activity (DPPH scavenging activity) of the bark successive extracted with n-hexane, ethyl acetate, methanol, and hot water as well as analyzed it with GC-MS. The result showed the highest amount of TPC (824.16±62.28 mg GAE/g), TFC (185.03±1.91 mg QE/g), and TTC (987.07±30.98 mg TAE/g) in the methanol extract of the bark. GC-MS analysis resulted hydroquinone as a major constituent in the methanol extract. Further, antioxidant activity was found the strongest on methanol extract (IC50=63.48), while correlation between antioxidant activity and TFC was found the highest (R2=0.93). These findings suggest that bark of C. sappan is a suitable source of natural antioxidant with strong activity to DPPH radical.